2019
DOI: 10.1080/00102202.2019.1610746
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Markers for Combustion Mode and Heat Release in MILD Combustion Using DNS Data

Abstract: Various commonly used markers for heat release are assessed using direct numerical simulation (DNS) data for Moderate or Intense Lowoxygen Dilution (MILD) combustion to find their suitability for nonpremixed MILD combustion. The laser-induced fluorescence (LIF) signals of various markers are synthesized from the DNS data to construct their planar (PLIF) images which are compared to the heat release rate images obtained directly from the DNS data. The local OH values in heat releasing regions are observed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…Another approach uses the chemical explosive mode analysis (CEMA) to differentiate between premixed propagation and diffusion flame characteristics. For example, compared the flame index to the chemical modes in a turbulent hydrogen flame and Doan and Swaminathan (2019) compared the regime prediction of the flame index with the chemical mode in MILD combustion and concluded that the CEMA based approach identified large parts of the flame as premixed whereas the flame index identified a non-premixed regime. Nordin-Bates et al (2017) applied a similar concept to a scram jet flame.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach uses the chemical explosive mode analysis (CEMA) to differentiate between premixed propagation and diffusion flame characteristics. For example, compared the flame index to the chemical modes in a turbulent hydrogen flame and Doan and Swaminathan (2019) compared the regime prediction of the flame index with the chemical mode in MILD combustion and concluded that the CEMA based approach identified large parts of the flame as premixed whereas the flame index identified a non-premixed regime. Nordin-Bates et al (2017) applied a similar concept to a scram jet flame.…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that the appearance of a distributed combustion is due to the interaction of thin reaction zones [19][20][21][22][23], which were also reported based on OH-PLIF visualisations [4,10,14,15]. These analyses have been further extended by Doan, Swaminathan and co-workers for stratified-mixture MILD combustion [24][25][26] and provided important insights into the flame structure [24,25], reaction-zone topology [24,25] and markers of combustion mode [26]. A review of the physical insights gained from DNS can be found in [27].…”
Section: Introductionmentioning
confidence: 63%
“…Several Reynolds averaged Navier-Stokes (RANS) and large eddy simulations (LES) investigations of MILD combustion using conventional flamelet and eddy dissipation approaches [8,9,13,16,17] have also been conducted which reported good agreement with experimental data in terms of mean velocity and temperature fields, but discrepancies have been reported in terms of peak temperature and minor species (e.g., CO and OH) concentrations [8,12]. The advancements in high-performance computing have enabled direct numerical simulations (DNS) of MILD combustion [18][19][20][21][22][23][24][25][26][27]. Van Oijen [18] carried out DNS of autoigniting mixing layers of CH 4 /H 2 fuel-blends and provided important insights to the roles of non-unity Lewis number and O 2 dilution on autoignition delay under MILD combustion conditions.…”
Section: Introductionmentioning
confidence: 98%
“…The image shown on the left is from the experimental studies of Scherrer et al (2016) and the one on the right is from the DNS case NP3. The numerical Schlieren, obtained as explained by Doan and Swaminathan (2019a), should be compared qualitatively to region marked as "Combustion" in the experimental image and the later image also shows shock waves. The similarities between these two images are quite interesting and offer support to the above deduction.…”
Section: Relevance To Supersonic Combustionmentioning
confidence: 98%
“…The OH-PLIF (planar laser-induced fluorescence) commonly used for the combustion diagnostics will pick the signals, coming from mixtures with low heat release, corresponding to the right peak and is likely to miss the signals from regions with large heat release rate since Y OH is almost the same as the background value, Y c OH . Thus, one needs extra care for studying MILD combustion using PLIF techniques (Doan and Swaminathan, 2019a).…”
Section: Mild Combustion Inceptionmentioning
confidence: 99%